At Eighteen: A Screenplay Dealing with Social Phobia in Adolescence - Cathleen Sarah Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2023)
Feeling nervous before performing in front of many people or worried in a new place is normal. However, if it significantly affects our daily lives, this might be a sign of fear of being judged or evaluated by people around us. This creative work, At Eighteen, intends to raise awareness of social phobia in adolescence by discussing the cause, effects, and a way to recover. All of these are based on theories by Rapee and Heimberg’s cognitive-behavioral model and Stallard’s cognitive behavioral therapy (CBT). The work is a screenplay about a high school writing champion, Elizabeth, who dreamed of attending college. Her journey was not easy as she moved to her mother’s hometown, transferred to public school, and failed to fulfill her own and her surroundings expectations with her writing skills. After seeing her avoiding people many times, Elizabeth was diagnosed with social phobia because she was afraid of getting negative evaluations. She recovered after attending several therapy sessions that helped change her dysfunctional thoughts to positive ones. This work falls under the drama genre to show Elizabeth’s personal life story and process of overcoming obstacles.